2009
DOI: 10.1002/cjoc.200990043
|View full text |Cite
|
Sign up to set email alerts
|

One Step Preparation of Controlled Drug Release Systems in Supercritical Carbon Dioxide

Abstract: Drug delivery systems based on copolymers of N-isopropylacrylamide were first prepared by a one step method, in which supercritical carbon dioxide was simultaneously used as a polymerization medium and an impregnation agent. The obtained microspheres were characterized by scanning electronic microscopy (SEM), differential scanning calorimetry (DSC), transmission electron microscopy (TEM) and X-ray diffraction (XRD). The release effect of the in situ prepared microgels impregnated with ibuprofen was presented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Cao et al has reported the values of n and K for poly-(NIPA-co-VP)-Ibu microgels at 37°C are 0.67 and 0.18 at pH 7.4, 1.5 and 0.01 at pH 1.2, respectively. It is demonstrated that the controlled release mechanism of poly(NIPA-co-VP)-Ibu microgels varies from synergism of drug diffusion and framework relaxation to framework relaxation as the pH value changes from 7.4 to 1.2 [40]. The relationship plots between ln(M t /M inf ) and lnt of the PNI-PA-Ibu and SiO 2 -PNIPA-Ibu microgels are shown in Fig.…”
Section: Ibu Release Simulationmentioning
confidence: 92%
“…Cao et al has reported the values of n and K for poly-(NIPA-co-VP)-Ibu microgels at 37°C are 0.67 and 0.18 at pH 7.4, 1.5 and 0.01 at pH 1.2, respectively. It is demonstrated that the controlled release mechanism of poly(NIPA-co-VP)-Ibu microgels varies from synergism of drug diffusion and framework relaxation to framework relaxation as the pH value changes from 7.4 to 1.2 [40]. The relationship plots between ln(M t /M inf ) and lnt of the PNI-PA-Ibu and SiO 2 -PNIPA-Ibu microgels are shown in Fig.…”
Section: Ibu Release Simulationmentioning
confidence: 92%